Phytochemical and antioxidant activity from fruit waste [peel] of citrus hystrix and ananas comosus by using DPPH assay / Nureen Shahirah Ahmad Zaghlul - Ahmad Zaghlul, Nureen Shahirah (2020)
Citrus hystrix (Kaffir lime) peels and Ananas comosus (pineapple) peels are wastes that are usually discarded in a large amount. Since previous studies have reported negative impact of negligible abundant wastes, there has been researches on waste potential. Interest in natural antioxidant from waste has directed this study. The aims of this study are to extract Kaffir lime peels and pineapple peels using Soxhlet extraction and maceration method, detect the phytochemicals using Gas Chromatography-Mass Spectrometry (GC-MS) and determine the antioxidant activity of both extracts singly and in combination. High percentage yield was obtained for both samples. Compounds found in Kaffir lime peels are in accordance with the previous studies which are citronellal, linalool, citronellol, terpinen-4-ol, iso Pulegol, and α-cubebene while new components were found in pineapple peels. The compounds are Benzene, 1,3—bis (phenoxyphenoxy), 2-Furancarboxaldehyde, 5-methyl-, 2-Furancarboxal- dehyde, 5-(hydroxymethyl)-, and 4H-Pyran-4-one, 2,3-dihydro-3, 5-dihydroxy-6-methyl-. The oxidative scavenging activity of both samples in single effect and combination effect were conducted using DPPH assay. It is found that Kaffir lime peels have higher value for percentage of inhibition and close to Ascorbic Acid which acts as standard in this study. At concentration 100 mg/mL Kaffir lime peels exhibit close value (92.87%) to the standard at concentration 10 mg/mL (92.40%). Pineapple peels have slightly lower value for percentage of inhibition against DPPH even at the highest concentration (89.10%). The combination for both samples were conducted and ratio 1:1 possess the highest value (63.14%) compared to other ratio. However, single effect of each extract is still higher than the combination ratio 1:1. This shows that single sample without combination has more positive value in antioxidant activity. In conclusion, wastes from Citrus hystrix peels and Ananas comosus peels do have potential to be natural antioxidants.